INVESTIGATING LANGUAGE TEACHERS' SOJOURN EXPERIENCES: PERSPECTIVES ON CULTURE - Arfiandhani, Puput (Journal of Foreign Language Teaching and Learning, 2017)
The more-connectedness of the world has raised a need to have a successful communication across cultural background. As a consequence, intercultural communicative competence (ICC) plays a more pivotal role. One of the means to proliferate ICC is through living abroad, or can be called as doing a sojourn. This qualitative study aims to explore language teachers' sojourn experiences during their two-semester assisting language classes in U.S. universities. Specifically, this study focuses on how their sojourn experiences may affect their perspectives toward their own culture and culture other than their own. There are 19 English language teachers of 12 different nationalities who voluntarily participated in the present study. In analyzing the data, Byram's model of ICC (1997) was utilized to make sense of their experiences. The data was analyzed using NVivo11 application. The finding showed that three out of five aspects in Byram's model of ICC (1997), including intercultural attitudes(savoir être), knowledge (savoirs), and critical cultural awareness (savoirs' engager) emerged in the data. Two aspects, skills of interpreting and relating (savoir comprendre) and skills of discovery and interaction (savoir apprendre/faire) did not emerge in the data.